Motivating the unemployed: A full‐range model of motivational strategies that caseworkers use to activate clients - Grandia, Jolien; La Grouw, Yvonne M.; Kruyen, Peter M. (Social policy & administration, 2020)
Governments use activation policies to stimulate unemployed citizens in finding work. Caseworkers are, as front‐line workers, responsible for concrete activation trajectories based on these activation policies. Little is known about how caseworkers try to get clients to participate in these activation trajectories. In a qualitative, inductive study (consisting of observations and reflective interviews) in two welfare agencies, we identified 10 motivational strategies that caseworkers employed. The full‐range leadership model appeared to be an appropriate perspective to understand, systematize, and reflect on these strategies, in particular as our analyses show that these motivational strategies can be placed on a continuum ranging from laissez‐faire to transactional and transformational strategies. We found that caseworkers matched their motivational strategy to the situation and client but preferred transformational strategies. Our findings implicate chances but also challenges for activation in practice and literature on front‐line workers.